Anaphylactoid reaction caused by sodium ceftriaxone in two horses experimentally infected by Borrelia burgdorferi - Basile, Roberta Carvalho [UNESP]; Rivera, Gabriela Gomes [UNESP]; Del Rio, Lara Antoniassi [UNESP]; Bonis, Talissa Camargo Mantovani de [UNESP]; Amaral, Gabriel Paiva Domingues do [UNESP]; Giangrecco, Edson [UNESP]; Ferraz, Guilherme [UNESP]; Yoshinari, Natalino Hajime; Canola, Paulo Aléscio [UNESP]; Queiroz Neto, Antonio [UNESP] (BioMed Central, 2015)
Lyme borreliosis is a disease transmitted by ticks to mammals, especially in horses and humans. Caused by a spirochete Borrelia burgdorferi, it can result in lameness, arthritis, carditis, dermatitis and neurological signs. Anaphylactoid reactions are severe responses caused by direct action of substances (drugs, toxins), which can pose risks to life. Still poorly documented in horses, these reactions are caused by the effects of inflammatory mediators such as histamine, kinins and arachidonic acid metabolites. The last two are the most clinically relevant for the species. The simultaneous occurrence of anaphylactoid reaction in two horses experimentally infected by Borrelia burgdorferi undergoing intravenous treatment with ceftriaxone sodium is reported. It was administered 4.7 × 10(8) spirochetes intradermal and subcutaneous applications in both horses to evaluate clinical aspects of the Lyme disease, 95 days before the application of sodium ceftriaxone. During the administration, one horse (a gelding) showed immediate and severe anaphylactoid symptoms such as urticaria, dyspnea, tachycardia, and eyelid edema, which were controlled by injecting dexamethasone. After 1 day, it expressed signs of abdominal discomfort, caused by severe bloat, which was treated surgically via celiotomy. Subsequently, this gelding had piroplasmosis and severe anemia, requiring treatment with an antimicrobial and blood transfusion. Second horse (a mare) showed signs of hypotension during the application of the antibiotic, which disappeared only when the application was interrupted. Days after the event, the mare developed moderate large colon bloat, which was treated with medication only. Subsequently the mare was evolved into the prodromal phase of laminitis in one of the forelimbs, which was treated for 10 days with non-steroidal anti-inflammatory and rheology modifying drugs and cryotherapy. From the two cases presented here, it does appear that sodium ceftriaxone can induce anaphylactoid reactions in horses infected by Borrelia burgdorferi, which may evolve into colic syndrome, laminitis and the occurrence of opportunistic infections. However, further evidence should be collected in order to draw definite conclusions.
Keywords: Hypersensitivity; Lyme; Colic; Laminitis